2018
DOI: 10.3390/ijms19092795
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic Effect of Hyperthermia on Enhancing Radiotherapeutic Efficacy

Abstract: Hyperthermia is a cancer treatment where tumor tissue is heated to around 40 °C. Hyperthermia shows both cancer cell cytotoxicity and immune response stimulation via immune cell activation. Immunogenic responses encompass the innate and adaptive immune systems, involving the activation of macrophages, natural killer cells, dendritic cells, and T cells. Moreover, hyperthermia is commonly used in combination with different treatment modalities, such as radiotherapy and chemotherapy, for better clinical outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 193 publications
0
40
0
Order By: Relevance
“…Finally, based on the increased number of F4/80+CD11b+ macrophages, we suggest that this cell population has also an important role in the anti-tumor effect of mEHT. Specifically, the p53-, p21-, and p27-expressing apoptotic/senescent cells in the treated tumors can be cleared away by macrophages [48], whose phagocytic/clearance function is also known to be enhanced by hyperthermia [49].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, based on the increased number of F4/80+CD11b+ macrophages, we suggest that this cell population has also an important role in the anti-tumor effect of mEHT. Specifically, the p53-, p21-, and p27-expressing apoptotic/senescent cells in the treated tumors can be cleared away by macrophages [48], whose phagocytic/clearance function is also known to be enhanced by hyperthermia [49].…”
Section: Discussionmentioning
confidence: 99%
“…HT elicits innate and adaptive immune responses which may enhance its treatment effects [3,42,43]. Studies have found that HT may increase the cytotoxic activity of natural killer (NK) and CD8þ T cells against tumor cells [44,45].…”
Section: Ht and Immunomodulationmentioning
confidence: 99%
“…These, on the one hand result in greater drug delivery to tumor and cells, and on the other hand increase the sensitivity of cells to chemotherapeutics and radiation, boosting the effect of chemotherapy and radiotherapy when combined with hyperthermia [ 71 , 72 ]. In addition, mild hyperthermia can induce or improve antitumor activity [ 73 , 74 , 75 , 76 ]. For example, many of the heat-shock proteins (HSPs) released from heat-stressed cancer cells can activate antigen-presenting cells (APCs) [ 77 , 78 , 79 ].…”
Section: Hyperthermia and Its Clinical Applicationmentioning
confidence: 99%